Ben Cao Gang Mu. - Li, Shizhen (Ben Cao Gang Mu: 16th Century Chinese Encyclopedia of Materia Medica and Natural History Series., 2024)
Volume VI in the Ben cao gang mu series offers a complete translation of chapters 26 through 33, devoted to vegetables and fruits. The Ben cao gang mu is a sixteenth-century Chinese encyclopedia of medical matter and natural history by Li Shizhen (1518-1593). The culmination of a sixteen-hundred-year history of Chinese medical and pharmaceutical literature, it is considered the most important and comprehensive book ever.